A Six-step Approach for scaling low-emission food systems: Evidence and guidelines - Amahnui, George Amenchwi; Sylvester, Janelle Marie; Vanegas Cubillos, Martha; Castro Nunez, Augusto (2025)
The global food system is a major contributor to climate change and is responsible for approximately one-third of all anthropogenic greenhouse gas (GHG) emissions. In many low- and middle-income countries, scaling innovations for climate-change mitigation requires identifying the right incentives, as well as navigating complex realities such as policies, regulations, and value chainrelated barriers. Consequently, efforts aimed at transforming food systems to low emissions may not yet deliver the desired impacts and, in some instances, may even produce undesirable effects on other Sustainable Development Goal (SDG) outcomes. This “Six-step Approach” to scaling lowemission food systems aims to bridge this gap. It provides a structured guide for creating an enabling environment that enhances scaling innovations for low-emission food system transformation, while delivering co-benefits and minimizing trade-offs and unintended side effects on SDG outcomes. These six steps include: (1) identifying direct and underlying drivers of food system GHG emissions and GHG emission sources; (2) identifying geographical areas where government development priorities overlap with food system GHG mitigation opportunities; (3) identifying farm-level drivers of adoption of innovations; (4) implementing value chain upgrading strategies to overcome adoption barriers; (5) promoting sustainable business models and financial mechanisms to scale innovations; (6) measuring climate action benefits, SDG co-benefits, and undesired effects. In this document, we present the approach and key considerations for its use in developing an enabling environment for scaling innovations toward low-emission food systems. Furthermore, we explore each step in-depth, discussing evidence, relevant methodological approaches, and information required for each step. To illustrate the approach’s application, we present a case study on scaling silvopastoral systems undertaken during the implementation of a project aimed at delivering climate-change mitigation and peacebuilding outcomes in the Colombian Amazon. The guidelines presented here emphasize the need for scaling practitioners to identify key delivery partners at the nexus between government SDG priorities (national and regional) and food system GHG mitigation opportunities, to secure political and social support for scaling low-emission food systems.